ANALISIS POSTUR KERJA PADA OPERATOR PEMUAT BUAH DENGAN REBA DAN RULA DI BAGERPANG PALM OIL - Uun Novalia Harahap; Yetti Meuthia Hasibuan; Denny Walady Utama; Arma Dani; Hendri Putra Jaya Gulo (Jurnal Simetri Rekayasa, 2022)
PT. PP London Sumatra is a factory that processes oil palm fruit into Crude Palm Oil (CPO). Oil palm fruit that comes from plantations is re-sorted by the sorting operator based on the level of fruit maturity. This sorting process is done manually using a gancu tool. At initial observation, it appears that workers have a poor working position so there is a musculoskeletal risk, so that data collection will be carried out using the Nordic Body Map Questionnaire, interviews, and documentation in the form of photos of the operator while working. Musculoskeletal risks were observed in several areas of the body, such as the back, waist, neck, upper arms, forearms, and wrists. Body posture analysis using Rapid Entire Body Assessment (REBA) and Rapid Upper Limb Assessment (RULA) methods was used in this study. The REBA method is used to analyze the lower and upper body postures, while the RULA method is to analyze the lower body postures. In the REBA analysis results obtained a score of 10 with a very high level of risk while RULA obtained a score of 7 with a high level of risk. Provision of repair solutions is carried out on sorting operators, namely changing body posture while working and suggestions for repairing work tools. At the analysis stage of improving posture, the REBA score fell to 7 with a mod.